Benthic diatom flora (Bacillariophyta) of Keban Reservoir (Elazig, Turkey) - Çetin, A. Kadri; Sen, Bulent (My University, 2006)
Benthic diatoms of the Keban Reservoir was investigated in the Keban and Icme Regions. A total of 102 taxa were recorded in the study area. The member of Pennales were the most conspicuous diatoms with respect to frequency of occurrence and numbers of individuals. Cyclotella krammerii, Amphora ovalis, Cymbella affinis, Fragilaria crotonensis, Navicula cryptocephala, and Nitzschia linearis were the most noticeable diatom species in Keban and Icme Regions. It was concluded that although some diatoms species were more abundant in one region than in the others, species composition of diatoms in the reservoir was not significantly different. ©Begell House Inc., 2006.
Keywords: Diatoms; Reservoir; Turkey